Could digital photography be an alternative to postoperative physical examination for pediatric tonsillectomy patients?. (August 2019) - Demir, Berat; Binnetoglu, Adem; Kersin, Burak; Mammadova, Ulker; Kucuk, Nurten
Abstract: Objective: To evaluate and compare the efficacy of postoperative control with digital photographs and physical examination for children who underwent tonsillectomy? Methods: In this prospective study, 86 children (46 boys (53.5%) and 40 girls (46.5%) were enrolled for postoperative clinical visit and for obtaining photographs of the tonsillar bed with a digital camera at clinic control. Results: No difference in tonsillar fossa healing was observed between the two methods 2 weeks after surgery. Conclusions: Digital photographs proved to be a safe method for postoperative control of pediatric patients who underwent tonsillectomy. Adding control with outpatient follow-up will be useful for minimizing postoperative complications.